Synthesis, crystal structure and EPR spectroscopic analysis of novel copper complexes formed from N-pyridyl-4-nitro-1,8-naphthalimide ligands - GUNNLAUGSSON, THORFINNUR (My University, 2014)
The mono-dentate, pyridyl containing, nitro naphthalimide ligands N-(4-pyridyl)-4-nitro-1,8-naphthalimide (L1) and N-(3-pyridyl)-4-nitro-1,8-naphthalimide (L2) were prepared and complexed with a selection of copper salts [Cu(OAc)2, Cu(CF3SO3)2 and Cu(ClO4)2]. Crystallographic studies were undertaken and revealed that dinuclear acetate bridged complexes resulted from reactions with Cu(OAc)2, while mononuclear systems resulted from reactions with Cu(CF3SO3)2 and Cu(ClO4)2. Despite the differing coordination environments the naphthalimide based ligands provided a range of interesting π-based interactions in the form of ππ, anionπ, nitroπ, solventπ and C[double bond, length as m-dash]Oπ associations. Solid state EPR spectra were in agreement with the coordination environments observed from crystallography.
PUBLISHED
Keywords: mono-dentate, pyridyl containing, nitro naphthalimide ligands; mono-dentate, pyridyl containing, nitro naphthalimide ligands